Rhodium-catalyzed hydroformylation of 1,3-butadiene to adipic aldehyde: revealing selectivity and rate-determining steps - Schmidt, Sebastian; Baráth, Eszter; Larcher, Christoph; Rosendahl, Tobias; Hofmann, Peter (Organometallics, 2015)
The reaction mechanism of Rh-catalyzed hydroformylation of 1,3-butadiene with triptycene-derived bisphosphite ligands L was studied by in situ NMR and IR experiments, kinetic measurements, and deuterioformylation. Under CO pressure the η3-crotyl complex (κ2-L)Rh(η3-crotyl)(CO) is a stable intermediate that slowly liberates 3-pentenal when hydrogen is added. It also represents the most stable intermediate under real hydroformylation conditions and exists in high concentrations during the catalysis. The rate law of the reaction is found to be second-order in syngas pressure and independent of the butadiene concentration. This agrees with the total barrier between the η3-crotyl complex and one of the transition states of hydrogen addition or reductive elimination being rate determining. The olefin insertion step is found to be partly reversible depending on the pressure, which means that n/iso regioselectivity is not controlled by this step alone.